2, 4‐Disubstituted 5‐Nitroimidazoles Potent against Clostridium difficile. (5th February 2019) - Spitz, Cédric; Mathias, Fanny; Péchiné, Séverine; Doan, Tri Hanh Dung; Innocent, Jean; Pellissier, Sylvain; Di Giorgio, Carole; Crozet, Maxime D.; Janoir, Claire; Vanelle, Patrice
Abstract: Metronidazole is one of the first‐line treatments for non‐severe Clostridium difficile infections (CDI). However, resistance limits its use in cases of severe and complicated CDI. Structure–activity relationships previously described for the 5‐nitroimidazole series have shown that functionalization at the 2‐ and 4‐positions can impart better activity against parasites and anaerobic bacteria than metronidazole. Herein we report the synthesis of new 2, 4‐disubstituted 5‐nitroimidazole compounds that show potent antibacterial activity against C. difficile . We used a vicarious nucleophilic substitution of hydrogen (VNS) reaction to introduce a phenylmethylsulfone at the 4‐position and a unimolecular radical nucleophilic substitution (SRN 1) reaction to introduce an ethylenic function at the 2‐position of the 5‐nitroimidazole scaffold. Abstract : 2, 4‐Disubstituted 5‐nitroimidazoles were synthesized using vicarious nucleophilic substitution of hydrogen (VNS) and unimolecular radical nucleophilic substitution (SRN 1) reactions. Herein we present the new nitroimidazoles obtained as well as the methodology used, their activity against Clostridium difficile, cytotoxicity, and results of micronucleus assays to evaluate genotoxicity. Three compounds showed higher activity than metronidazole against four C. difficile strains.